Comparative study of leaching of silver nanoparticles from fabric and effective effluent treatment - Pasricha, Aneesh; Jangra, Sant Lal; Singh, Nahar; Dilbaghi, Neeraj; Sood, K.N.; Arora, Kanupriya; Pasricha, Renu (Journal of environmental sciences (China), 2012)
Nano silver （Agn） is employed as an active antimicrobial agent, but the environmental impact of Agn released from commercial products is unknown. The quantity of nanomaterial released from consumer products during use should be determined to assess the environmental risks of advancement of nanotechnology. This work investigated the amount of silver released from three different types of fabric into water during washing. Three different types of fabric were loaded with chemically synthesized Ag nanoparticles and washed repeatedly under simulated washing conditions. Variable leaching rates among fabric types suggest that the manufacturing process may control the release of silver reaching the waste water treatment plants. In an attempt to recover the Agn for reutilization and to save it from polluting water, the effluents from the wash were efficiently treated with bacterial strains. This treatment was based on biosorption and was very efficient for the elimination of silver nanoparticles in the wash water. The process ensured the recovery of the Agn leached into the effluent for reutilization, thus preventing environmental repercussions.